2009
DOI: 10.1016/j.jalgebra.2008.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Orbits of the actions of finite solvable groups

Abstract: 2016-11-15T19:40:59

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…In [25], Yang strengthened this result by showing the following. Suppose that V is a faithful completely reducible G-module where G is a finite solvable group, then there exist v ∈ V and K G such that C G (v) ⊆ K, where the Fitting length of K is less than or equal to 7.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In [25], Yang strengthened this result by showing the following. Suppose that V is a faithful completely reducible G-module where G is a finite solvable group, then there exist v ∈ V and K G such that C G (v) ⊆ K, where the Fitting length of K is less than or equal to 7.…”
Section: Introductionmentioning
confidence: 86%
“…Suppose that V is a faithful completely reducible G-module where G is a finite solvable group, then there exist v ∈ V and K G such that C G (v) ⊆ K, where the Fitting length of K is less than or equal to 7. An example [25,Section 4] was provided to show that the improvement is the best possible. Although one cannot say more in general because of this example, it is possible to show that there exits an element v ∈ V such that the p-part of C G (v) is relatively small for all the primes p ≥ 5.…”
Section: Introductionmentioning
confidence: 99%
“…We also construct groups with no regular orbits on V when e = 8, 9 and 16. When one studies the orbit structure of solvable linear groups, the common strategy is to use reduction. As we can see in many places (for example [1,6,7,9]), many problems are reduced to the situation where the action is irreducible and quasi-primitive and then properties are checked for all possible values of e. Our result is quite useful since the existence of regular orbit is a nice property which will imply many other properties. Clearly when e = 1, it is easy to find primitive solvable group which has no regular orbits on the vector space.…”
Section: Introductionmentioning
confidence: 92%
“…A/F ∈ SCRSp(2, 2) × SCRSp (6,3) and |A/F | 6 · 24 3 · 6 by Lemma 2.17(1), (9). By Lemma 2.3, |G| 6 · 24 3 · 6 · 54 2 · 6 < |W | 13 , a contradiction.…”
Section: Lemma 215 Suppose That H Is a Linear Group On V 1 And S Isunclassified
“…In particular, they showed that G F G p ≤ c p G 19 when G is any solvable group and that G F G p ≤ c p G 2 when G is odd. More recently, the work of Yang in Corollary 5.6 of [14] can be used to improve this bound to G F G p ≤ c p G 15 . An example in [4] shows that the bound is best possible when G is odd.…”
Section: Bounding An Indexmentioning
confidence: 99%